Frontline Advising: Understanding the Challenges and Policy Issues Placed on International Students during the COVID-19 Crisis (Comparative & International Education Series, 2021)
Chapter 9|20 pages Frontline Advising for International Students at American Community Colleges: Understanding the Challenges and Policy Issues during the COVID-19 CrisisBy Gregory F. Malveaux, Marlon VallejoAmerican community colleges in higher education with large numbers of international students have dedicated International Education and International Student offices that provide essential advising and serve as the primary liaison for handling various aspects of the immigration process. International students (F-1 visa holders, and other categories), along with their advisers, have recently been forced to spend considerable time and energy adapting to changing US policies to remain compliant. In addition, they have needed to navigate through new and unique hurdles fueled by COVID-19 restrictions. The result has been a damaging ripple effect in American higher education and the US economy at large. Chapter findings apply first-hand accounts from frontline advisers—Principal Designated School Officials (PDSO), International Education Directors, Study Abroad Coordinators, and faculty—who are in leading positions to guide F-1 visa holders and other international student groups. There will need to be future research done to safeguard the enrollment, access, and equity of the international student population at US community colleges.